IMPLEMENTASI MRP DALAM MEMINIMALKAN BULLWHIP EFFECT SERTA AHP UNTUK PEMILIHAN PEMASOK HANDAL (STUDI KASUS PT GHJ) - Lulu Chyntia Desari (2020)
The business industry in the COVID-19 pandemic the limitations of business activities affect PT GHJ's supply chain performance to meet consumer demand. PT GHJ is a company engaged in the distribution of health products in the form of tourmaline stones. In company's activities, raw material requirements planning application has not been carried out properly and the impact of a pandemic on the cooperation between PT GHJ with suppliers led to the occurrence of irregularities forecast demand and increasing the value of the costs incurred by PT GHJ. The problem of this study is aimed at whether Material Requirement Planning can minimize the value of the Bullwhip Effect that occurs at PT GHJ and which alternat4e suppliers are reliable in improving supply chain performance at PT GHJ based on the AHP method. Based on the results of data collection and processing it is known that the Material Requirement Planning process can minimize the value of the Bullwhip Effect of 1.266 with the final value of the Bullwhip Effect of 0.214 and minimize the total overall cost of the product of Rp510.043.560,- or 24% with a total value of the total final cost of the product of Rp1.651.506.320,-. S suppliers are considered the most reliable compared to other alternative suppliers by the respondents based on the AHP method with a global value of 0.412. The main priority criteria used in considering a reliable supplier of quality criteria is the weight value of 0.192 and sub-criteria suitability of the product (A2) with a weight of 0.599.